2009
DOI: 10.1007/s10389-009-0302-5
|View full text |Cite
|
Sign up to set email alerts
|

Potential impact of a pilot training program on smoking cessation intervention for tuberculosis DOTS providers in Malaysia

Abstract: Background The association between tuberculosis (TB) and tobacco smoking is becoming increasingly important.Smoking cessation may yield substantial positive effects on TB treatment outcomes, relapse, and future lung disease. Thus, TB directly observed therapy, short-course (TB DOTS) providers are uniquely positioned to intervene with those TB patients who are smokers. Unfortunately, most health care professionals are inadequately trained to provide such service.Aim This study aimed to determine the feasibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Consistent with other TB HCP training evaluations that assessed knowledge improvement immediately after training, our study showed an increase in the proportion of participants with higher test scores in the immediate post-training test, which adds to the evidence that training programmes are effective in improving factual TB/MDR-TB knowledge in short term 33–35. Because no previous evaluation has assessed long-term knowledge retention of TB HCP training programmes, we were unable to compare the knowledge changes observed a year after training in our study with other similar assessments.…”
Section: Discussionsupporting
confidence: 76%
“…Consistent with other TB HCP training evaluations that assessed knowledge improvement immediately after training, our study showed an increase in the proportion of participants with higher test scores in the immediate post-training test, which adds to the evidence that training programmes are effective in improving factual TB/MDR-TB knowledge in short term 33–35. Because no previous evaluation has assessed long-term knowledge retention of TB HCP training programmes, we were unable to compare the knowledge changes observed a year after training in our study with other similar assessments.…”
Section: Discussionsupporting
confidence: 76%
“…Patients were identified based on their self-reported tobacco use during TB diagnosis. They were then referred at the point of initiating DOTS regimen by the attending physician to TB DOTS providers who were specially trained to provide SCI in TB setting [ 34 ]. Patients were recruited into the study upon fulfillment of eligibility criteria and written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…9 Despite these opportunities, Malaysian pharmacists were not contributing optimally in this area. 10,11 Lack of comprehensive tobacco-related courses and training in most universities' curricula was cited as a major contributing factor, as well as lack of in-service training and continuing professional development (CPD) programs focusing on the subject. 10 The latter issue was addressed through the initiation of the Certified Smoking Cessation Service Provider (CSCSP) program in 2004.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Lack of comprehensive tobacco-related courses and training in most universities' curricula was cited as a major contributing factor, as well as lack of in-service training and continuing professional development (CPD) programs focusing on the subject. 10 The latter issue was addressed through the initiation of the Certified Smoking Cessation Service Provider (CSCSP) program in 2004. The main objective of CSCSP was to provide Malaysian health care professionals with additional, specialized counseling skills to help smokers quit the habit.…”
Section: Introductionmentioning
confidence: 99%